Borrowed Legal Discourse in Pakistani Bar and Bench:An Explanatory Analysis (Journal of Asian Development Studies, 2023)
Like many other legal systems worldwide, the sophisticated language element of Pakistan'slegal register contains a substantial percentage of expressions borrowed from other linguistictraditions. In this study piece, using borrowed terms in Pakistani legal register speech isdifficult. The country's legal discourse's historical continuity, accuracy, and clarity aresignificantly influenced by these language components, which are frequently taken from Latin,Persian, and English. Like many legal systems worldwide, the Pakistani legal register ischaracterized by a diverse linguistic fabric, with a large amount of terminology acquired fromother languages. This research looks into the problem of explanatory borrowed legal speechamong Pakistan's Bar and Bench. We are focused on comprehending how little linguisticdifferences impact communication and how foreign legal terminology influences juries,attorneys, and the legal system. Additionally, the goal of this study is to explore the complexnetwork of borrowed terms that are used in Pakistani law. These linguistic components arefrequently drawn from Latin, Persian, and English and are crucial for evaluating the nation'slegal discourse's accuracy, coherence, and historical continuity. This research examines andexplains the problem of borrowed legal speech in Pakistani bench and bar talk. The studyinvestigates the rationale behind adopting this borrowed terminology. It focuses oncomprehending the language intricacies and the effects of foreign legal phrases on judges,legal practitioners, and legal procedures. The study clarified how incorporating foreign legallanguage impacts the communication techniques within the Pakistani legal community bythoroughly analyzing legal texts, court hearings, and professional communication. Insightsinto the consequences of borrowed legal language for professional identity, legal clarity, andPakistan's larger legal culture are provided by the analysis, which takes into accounthistorical, cultural, and practical reasons that contribute to its predominance.